Health data issues in Africa: time for digitization, standardization and harmonization - Abdoelnaser Degoot; Ismaël Koné; Shakuntala Baichoo; Mercy Ngungu; Nzisa Liku; Judit Kumuthini; Joyce Nakatumba-Nabende; Foutse Khomh; Bubacarr Bah (Nature Communications)
This commentary discusses health data challenges in Africa, focusing on digitization, standardization, and harmonization as key solutions. It highlights how addressing these foundational issues can enable AI and data science to transform healthcare systems across the continent.